2020
DOI: 10.1111/ppa.13191
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study for spot blotch resistance in Afghan wheat germplasm

Abstract: Spot blotch (SB), caused by Bipolaris sorokiniana, is a devastating disease of wheat globally, especially in South Asia and South America. Understanding the genetics of resistance to SB is important for developing breeding strategies to improve resistance. A panel of 301 genotypes from Afghanistan was phenotyped over two crop seasons using a mixture of virulent B. sorokiniana isolates and genotyped using DArTSeq to obtain genome‐wide markers. Fifty genotypes (16.6%) showed disease scores less than the resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 23 publications
11
22
1
Order By: Relevance
“…It is noteworthy that the SNP marker S1B_636840957 on chromosome 1B was associated with spot blotch severity, where the annotation study revealed that S1B_636840957 is close to transmembrane protein, which regulates fungal development and pathogenicity via the MAPK module ( Gu et al, 2015 ). Another significant marker S1D_8983568 accounted for 24.0% of the allelic effect, consistent with the earlier studies ( Bainsla et al, 2020 ). However, the QTL reported in our study and Bainsla et al (2020) was more than 83 Mb apart at chromosome 1D.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It is noteworthy that the SNP marker S1B_636840957 on chromosome 1B was associated with spot blotch severity, where the annotation study revealed that S1B_636840957 is close to transmembrane protein, which regulates fungal development and pathogenicity via the MAPK module ( Gu et al, 2015 ). Another significant marker S1D_8983568 accounted for 24.0% of the allelic effect, consistent with the earlier studies ( Bainsla et al, 2020 ). However, the QTL reported in our study and Bainsla et al (2020) was more than 83 Mb apart at chromosome 1D.…”
Section: Discussionsupporting
confidence: 91%
“…Another significant marker S1D_8983568 accounted for 24.0% of the allelic effect, consistent with the earlier studies ( Bainsla et al, 2020 ). However, the QTL reported in our study and Bainsla et al (2020) was more than 83 Mb apart at chromosome 1D.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A recent study phenotyped 301 Afghan wheat germplasms and found that approximately 15% of them exhibited lower disease scores than the resistant control. A subsequent GWAS approach identified twenty-five marker-trait associations on more than twelve chromosomes, including previously identified Vrn-A1 and Sb2/Tsn1 loci [43].…”
Section: Progress In Dissecting the Genetic Determinants Of Wheat Resmentioning
confidence: 99%